Japan’s Disappointing Entrée into the Global Arms Market - Bitzinger, Richard A. (2016)
Japan’s failure to win the Australian submarine contract highlights the challenges of entering the global arms market. Japan may secure export sales in the future, but it will likely have to start small and be realistic.